Use of a block-iterative algorithm for retrieving aerosol integral size distributions from sun spectrophotometry data - Veretennikov, V. V.; Men’shchikova, S. S. (Atmospheric and oceanic optics, 2010)
A modified method is presented for retrieving aerosol integral size distributions in solar photometry problems. The presence of fine and coarse fractions of particles in the atmosphere is assumed. The initial matrix of the system is subdivided into four blocks in accordance with two particle fractions and two spectral regions, i.e., short and long wavelengths. Each of the two fractional integral size distributions is retrieved separately using a block-iterative inversion algorithm with a further iterative correction. The capabilities of the suggested method are numerically estimated in comparison with the results of the inversion for the entire particle ensemble.